Attractive running environments for all? A cross-sectional study on physical environmental characteristics and runners' motives and attitudes, in relation to the experience of the running environment - Ineke Deelen; Mark Janssen; Steven Vos; Carlijn B. M. Kamphuis; Dick Ettema (BMC, 2019)
Abstract Background Running has become one of the most popular sports and has proven benefits for public health. Policy makers are increasingly aware that attractively designed public spaces may promote running. However, little is known about what makes a running environment attractive and restorative for runners and to what extent this depends on characteristics of the runner. This study aims to investigate 1) to what extent intrapersonal characteristics (i.e. motives and attitudes) and perceived environmental characteristics (e.g. quality of the running surface, greenness of the route, feelings of safety and hinderance by other road users) are associated with the perceived attractiveness and restorative capacity of the running environment and 2) to what extent the number of years of running experience modify these associations. Methods Cross-sectional data were collected through the online Eindhoven Running Survey 2015 (ERS15) among half marathon runners (N = 2477; response rate 26.6%). Linear regression analyses were performed for two outcomes separately (i.e. perceived attractiveness and perceived restorative capacity of the running environment) to investigate their relations with motives and attitudes, perceived environmental characteristics and interactions between perceived environmental characteristics and number of years of running experience. Results Perceived environmental characteristics, including green and lively routes and a comfortable running surface were more important for runners' evaluation of the attractiveness and restorative capacity of the running environment than runners' motives and attitudes. In contrast to experienced runners, perceived hinder from unleashed dogs and pedestrians positively impacted the attractiveness and restorative capacity for less experienced runners. Conclusions Perceived environmental characteristics were important determinants of the attractiveness and restorative capacity of the running environment for both novice and experienced runners. However, green and lively elements in the running environment and hinderances by cars were more important for less experienced runners. In order to keep novice runners involved in running it is recommended to design comfortable running tracks and routes and provide good access to attractive, green and lively spaces.